Enhancement of bid decision-making in construction projects: a reliability analysis approach - Ghodoosi, Farzad; Bagchi, Ashutosh; Hosseini, M. Reza; Vilutienė, Tatjana; Zeynalian, Mehran (Journal of Civil Engineering and Management, 2021)
Various risks significantly influence pricing of bids and a wide range of factors impact bid pricing risks. Of these, client’s reputation and the record of projects owned by a client have vital contribution on the issue. Current practices however fail to capture the impacts of client-related factors. There is a need for developing a practical quantitative approach, which enables estimators to process bid risk allocation easily. Through reliability analysis, the developed method proposed in this study enables practitioners to make informed bid/no-bid decisions based on estimating the probabilities of schedule and cost overruns. Estimating the probability of project failure enables estimators to quantify the risk element of bid price. In addition, schedule and cost overrun cumulative probability distributions can be used to estimate the expected value of these variables. The practicability of this proposed method is tested by empirical data obtained from 40 university construction projects of one client, for estimating the bid price of a low-rise building. For researchers, findings provide illuminating insight into the potential of using reliability analysis as a valuable tool for bid decision-making practices. So too, the proposed method offers a blueprint for estimating and calculating time and contingency – and managing associated risks – in planning construction projects. The contribution of this study for the world of practice lies in providing a simple, rapid and cost-effective method for bid decision-making processes.